Bi'ah Lughawiyah of al-Azhar Arabic Course in The Socio-Cultural Vygotsky - Alamsyah, Zulfian; Afyuddin, Moh. Sholeh; Hartanto, Eko Budi; Ma'arif, M. Syamsul (Asalibuna, 2022)
This research aims to examine Biah Lughawiyah at the Al-Azhar Arabic Language Course Institute, Pare from the perspective of Vygotsky's socio-cultural theory, namely Zone of proximal development, Scaffolding, and Language and Thought and Cognitive Development. This research uses descriptive qualitative methods. The data source was determined using Purposive Sampling techniques. Data collection techniques use interview, observation and documentation methods. Data analysis techniques use data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this research conclude that Bi'ah Lughawiyah activities at the al-Azhar Pare Arabic Language Course Institute are in accordance with Vygotsky's Socio-Cultural theory, namely: 1) it is mandatory to speak Arabic while at al-Azhar Pare in accordance with the principles of language and thought and cognitive development theory Vygotsky, 2) Mufrodat and al-Azhar Got Talent deposits are in accordance with the principles of zone of proximal development and scaffolding, 3) educational punishments are in accordance with the principles of zone of proximal development, 4) al-imtihan is in accordance with the principles of scaffolding, 5) jurfah class is in accordance with Vygotsky's theory of cognitive development, 6) provision of guidebooks in accordance with the zone of proximal development, 7) awards or rewards in accordance with Vygotsky's principles of language and thought, 8) halaqoh room in accordance with Vygotsky's theory of cognitive development, and 9) an Arabic nuanced environment in accordance with principle of the zone of proximal development.